2009
DOI: 10.1074/mcp.m800450-mcp200
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Domain-Peptide Interaction Interface

Abstract: Extensive efforts have been devoted to determining the binding specificity of Src homology 3 (SH3) domains usually in a case-by-case manner. A generic structure-based model is necessary to decipher the protein recognition code of the entire domain family. In this study, we have developed a general framework that combines molecular modeling and a machine learning algorithm to capture the energetic characteristics of the domain-peptide interactions and predict the binding specificity of the SH3 domain family. Ou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
60
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 101 publications
(62 citation statements)
references
References 49 publications
(48 reference statements)
0
60
0
1
Order By: Relevance
“…[9][10][11][12][13][14][15] Certainly, the MM/GBSA or MM/PBSA calculations based on molecular dynamics (MD) simulations or only molecular mechanics (MM) minimizations are more time-consuming than most scoring functions. However, with the rapid advance of computer hardware, it is feasible to use MM/GBSA or MM/PBSA as a scoring function in molecular docking calculations or even docking-based VS.…”
Section: Introductionmentioning
confidence: 99%
“…[9][10][11][12][13][14][15] Certainly, the MM/GBSA or MM/PBSA calculations based on molecular dynamics (MD) simulations or only molecular mechanics (MM) minimizations are more time-consuming than most scoring functions. However, with the rapid advance of computer hardware, it is feasible to use MM/GBSA or MM/PBSA as a scoring function in molecular docking calculations or even docking-based VS.…”
Section: Introductionmentioning
confidence: 99%
“…Previously, Wang and co-workers reviewed a lot of works on the statistical modeling and prediction of SH3 domainpeptide interaction behavior, and found that nonlinear machine learning methods appear to more effective than linear PLS in terms of predictive accuracy and reliability [14,17]. Therefore, in this work we employed a sophisticated SVM technique to mine the hidden nonlinear relationship between the structural descriptors and the binding affinities of the peptide samples.…”
Section: Comparison Of Linear Pls To Nonlinear Svmmentioning
confidence: 97%
“…For example, Hou et al employed molecular dynamics simulation and CoMFA/CoMSIA to examine the binding mode and potency of peptide to hAmph SH3 [16]. Later, this work was further generalized to decipher the protein recognition codes of diverse SH3 domains [17]. Zhou et al employed divided physicochemical property scores coupled with genetic algorithm-Gaussian processes to perform a comparative study of a panel of culled SH3-binding peptides, and concluded that diverse properties contribute remarkably to the interactions between the hAmph SH3 and its peptide ligands [18].…”
Section: Introductionmentioning
confidence: 97%
“…The MM/GBSA free energy decomposition procedure (Hou et al, 2009(Hou et al, , 2012 was used to calculate the [C n mim]-residue pairs interaction energies (DG r ) between IL and each individual residue (Rastelli et al, 2010).…”
Section: Molecular Modelingmentioning
confidence: 99%